Simulation and control of sensory-mode interaction - Mohamad Hanif, Noor Hazrin Hany; Elamvazuthi, Irraivan; Sulaiman, Suziah; Shoon, So Oo (International Journal of Engineering & Technology (IJENS), 2009)
Haptics, the sensation of physical touch to the virtual objects, is the most recent enhancement to virtual environment. With haptic simulation, virtual objects with different properties could be created to touch using haptic device. In current medical practice, haptics technology is being used to aid surgeons to perform surgical procedures such as needle insertion. It is vital that the penetration of the needle does not cause injury to the patients. However, the available technology does not address issues such as tissue texture and the depth of penetration. This project is about the simulation of sensory mode interaction of virtual objects of different stiffness and friction using PHANToM Haptic device. The penetration depth and force exerted into the objects should be within limit to avoid any deformity to the objects. PID controller is incorporated into the system to eliminate steady state errors as well as to ensure better transient response. To conduct the specified work, MATLAB software was used. Experimental results on the sensory mode interaction have proven the ability of the system to touch the objects within specified object limits. Simulated results on the system response have also shown the capability of the controller to provide fast and accurate response of the haptic device